A DFT study of hydrogen storage in Zr(Cr0.5Ni0.5)2 Laves phase. (30th January 2016) - Merlino, A. Robina; Luna, C.R.; Juan, A.; Pronsato, M.E.
Abstract: Theoretical studies on the total energy, electronic structure and bond of Zr(Cr0.5 Ni0.5 )2 intermetallic compound and its hydrides were performed using density functional calculations. The optimized c/a ratio was found in good agreement with experimental data of the C14 Laves phase. When hydrogen is introduced in the AB2 matrix (A = Zr; B = Ni, Cr) the A2 B2 sites are preferentially occupied in the structure, followed by the AB3 while B4 remains empty. The volume of the intermetallic increases up to 52.19% when 28H are absorbed in the unit cell, whereas the binding energy remains practically the same up to −6.76 eV/H, indicating little interaction. Among hydrogenations the main contribution to density of states is due to d electrons of all components of the structure. H-metal bonding is detected in the range −8 to −6 eV. Above 8H the magnetic moment increases with respect to the pure Laves phase. Highlights: The Zr(Cr0.5 Ni0.5 )2 Laves phase demonstrated to be more stable than ZrCr2 structure. The most stable absorption site for a hydrogen atom was the A2 B2 tetrahedral of composition ZrZrCrCr. After the structure hydrogenation, metal–metal bonds were weakened and metal-H bonds were formed. The structure showed a hydrogen storage capacity of 28H per unit cell and a lattice expansion of 52%.